2015
DOI: 10.4172/2165-7556.1000e130
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Interventions, Health and Injury Prevention during Off-Road Mountain Biking

Abstract: EditorialHalf of all Americans participated in outdoor recreation activities during 2013, of which 16% or 46.6 million (older than 6 yrs) take part in cycling (Road, Mountain bike, or BMX). Excursions totalled at 2.7 billion and ranked it 2 nd for number of outings (887.9 million) for ages 6-17 yrs [1]. This presents a positive picture in regards to health promotion, yet there are concerns regarding bone health and excessive time spent in a weight supported position in road cyclists [2]. On the other hand, mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Riders who have a higher level of physical fitness tended to recover to a greater extent as seen by the negative correlation between measured in the laboratory and measured during DH R . We surmise that the reduced vibration exposure eventuated to a decreased musculo‐tendonous work requirement (Hurst et al., 2012), which would normally absorb the accelerations in order to protect the head and lumbar spine (Macdermid, 2015; Macdermid et al., 2014b, 2015b, 2016; Miller & Macdermid, 2015). However, as muscle activity was not directly measured, this explanation remains only speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Riders who have a higher level of physical fitness tended to recover to a greater extent as seen by the negative correlation between measured in the laboratory and measured during DH R . We surmise that the reduced vibration exposure eventuated to a decreased musculo‐tendonous work requirement (Hurst et al., 2012), which would normally absorb the accelerations in order to protect the head and lumbar spine (Macdermid, 2015; Macdermid et al., 2014b, 2015b, 2016; Miller & Macdermid, 2015). However, as muscle activity was not directly measured, this explanation remains only speculative.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect MTB participants are subjected to vibrations from the grounds that are transferred from terrain surface-bicycle-rider [7,8]. These movements have the potential for causing disturbances to the central nervous system and have been linked to transient vertigo [6].…”
Section: Editorialmentioning
confidence: 99%
“…While many turn to cycling for its rehabilitative potential in comparison to impact sports such as running, the rate of injury in cycling is still rather high [1] and especially so in mountain biking (MTB) [2][3][4][5][6]. While traumatic injuries often receive the most attention, instances of overuse injuries are of particular concern in mountain biking as symptoms can often go unnoticed [2,3,5].In this respect MTB participants are subjected to vibrations from the grounds that are transferred from terrain surface-bicycle-rider [7,8]. These movements have the potential for causing disturbances to the central nervous system and have been linked to transient vertigo [6].…”
mentioning
confidence: 99%
“…Hence, use of suspension translates to better braking performance, cornering and predictability of the bicycle. Thirdly, by absorbing energy, suspension can reduce the risk of injury due to impacts being transmitted through the bicycle (Macdermid 2015(Macdermid , 2017. This 'fatigue theory' exploring the increased comfort achieved when using suspension has been studied to the largest extent and is expanded below.…”
Section: Why Use Suspension For Mountain Biking?mentioning
confidence: 99%
“…This highlights the importance of well performing suspension on downhill mountain bikes. Macdermid (2015) contends that the high overall injury rate in mountain biking and in particular lower back, neck and wrist pain can be partly attributed to riders' exposure to complex vibrations varying in frequency, direction and amplitude. Additionally, experiments have found that of the energy used by the rider to power the bicycle, the amount dissipated by suspension is negligible on most uneven terrain (Ishii et al 2003).…”
Section: Why Use Suspension For Mountain Biking?mentioning
confidence: 99%